Preferred Learning Style of Undergraduate Medical Students of a Medical College in Jammu and Kashmir India (Indian Journal of Public Health Research & Development, 2025)
Background: Learning style is a term that refers to the different ways in which we learn, process and retain information. Learning style is considered as an important factor for success in higher education. Method: Convenient sampling was used to select the participants from three different years of MBBS course. Data was collected using VARK Questionnaire in a Google Form. Descriptive and analytic statistics was used to analyse result. Conclusion: The most favoured learning style was kinaesthetic. The most preferred teaching method was interactive lectures. There was no association between learning styles and gender.
Keywords: Learning Style, Teaching Method, VARK learning style, Kinaesthetic Learner.